2015
DOI: 10.1080/08869634.2015.1097275
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the masticatory path at the mandibular first molar throughout the masticatory sequence of a hard gummy jelly in normal occlusion

Abstract: Masticatory paths of the mandibular first molar at slice levels greater than 3.0 mm were evidently modulated to adapt to the changing properties of the food, and those at the 2.0 mm slice level remained stable throughout the masticatory sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Kitashima et al [ 24 ] investigated mandibular movements during the process of mastication of hard gummy jelly in terms of the movement stages, that is, the initial, middle, and final stages, and reported that both the opening distance and the masticatory width were the greatest in the initial stage, decreasing in the middle to the final stage. They also reported that while there was no significant difference in the opening distance between the initial and middle stages of mastication, the masticatory width differed significantly between these two stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitashima et al [ 24 ] investigated mandibular movements during the process of mastication of hard gummy jelly in terms of the movement stages, that is, the initial, middle, and final stages, and reported that both the opening distance and the masticatory width were the greatest in the initial stage, decreasing in the middle to the final stage. They also reported that while there was no significant difference in the opening distance between the initial and middle stages of mastication, the masticatory width differed significantly between these two stages.…”
Section: Discussionmentioning
confidence: 99%
“…On closer scrutiny, however, all the results of the previous studies show a tendency for the cycle time to be longer during the chewing of hard food than during that of soft food. Kitashima et al [ 24 ] examined the cycle time for mastication of hard gummy jelly and reported that there was no significant difference in the cycle time among the stages of mastication, but that the cycle time in the initial stage, when the food was still hard, tended to be longer than that in the middle and final stages. Slavicek et al [ 25 ] investigated the movement for mastication of three types gummy jellies created by changing the amount of gelatin and reported that the number of chewing strokes varied only marginally.…”
Section: Discussionmentioning
confidence: 99%